MALE URETHRAL STRICTURE CHARACTERISTIC IN DR KARIADI GENERAL HOSPITAL SEMARANG: A DESCRIPTIVE STUDY - Parulian Pasaribu, Erwin; Daniswara, Nanda; Santosa, Ardy; Agung Nugroho, Eriawan; Soedarso, M. Adi; Rais Adin, Sofyan (Indonesian Journal of Urology, 2021)
Objective: This research was conducted to describe male urethral stricture characteristic in Kariadi General Hospital Semarang. Material & Methods: The data is collected retrospectively from the male urethral stricture patient medical records Kariadi General Hospital Semarang between January 2013 until December 2017. The data is analyzed descriptively to describe the characteristics of male urethral stricture patients, patient age, etiology, site, definitive surgery, and complications. Results: Within the period, 171 patients with male urethral stricture. The mean age was 52.11 years (range 9-86). The causes of stricture were trauma in 145 patients (84.8%), infection in 25 patients (14.6%) and iatrogenic in 1 patients (0.06%). Strictures site were posterior in 146 patients (85.4%) and anterior in 25 patients (14.6%). The definitive surgery for strictures were from DVIU in 132 patients (77.2%) and urethroplasty in 39 patients (22.8%). Complications rate were recurrence of stricture 56 patients (32.74%), bleeding 6 patients (3.05%), extravasation 14 patients (8.18%), erectile dysfunction 4 patients (2.34%). Conclusion: Trauma is the leading cause of urethral stricture in Kariadi General Hospital. The most common definitive therapy for urethral stricture in Kariadi General Hospital was still DVIU, but there has been an increase for urethroplasty and we still get the learning curve for it.